The Life of Mark Twain : The Middle Years, 1871-1891 - Scharnhorst, Gary (Book collections on Project MUSE., 2019)
"The second volume of Gary Scharnhorst's three-volume biography chronicles the life of Samuel Langhorne Clemens between his move with his family from Buffalo to Elmira (and then Hartford) in spring 1871 and their departure from Hartford for Europe in mid-1891. During this time he wrote and published some of his best-known works, including Roughing It, The Gilded Age, The Adventures of Tom Sawyer, A Tramp Abroad, The Prince and the Pauper, Life on the Mississippi, Adventures of Huckleberry Finn, and A Connecticut Yankee in King Arthur's Court. Significant events include his trips to England (1872-73) and Bermuda (1877); the controversy over his Whittier Birthday Speech in December 1877; his 1878-79 Wanderjahr on the continent; his 1882 tour of the Mississippi valley; his 1884-85 reading tour with George Washington Cable; his relationships with his publishers (Elisha Bliss, James R. Osgood, Andrew Chatto, and Charles L. Webster); the death of his son, Langdon, and the births and childhoods of his daughters Susy, Clara, and Jean; as well as the several lawsuits and personal feuds in which he was involved. During these years, too, Clemens expressed his views on racial and gender equality and turned to political mugwumpery; supported the presidential campaigns of Grover Cleveland; advocated for labor rights, international copyright, and revolution in Russia; founded his own publishing firm; and befriended former president Ulysses S. Grant, supervising the publication of Grant's Memoirs"--